Antioxidants activity of schiff base and metal schiff base complexes - Al-Nazirul Mubin Ahmad Supri (2014)
Antioxidants are chemical compounds which can delay the start or slow the rate of oxidation reaction. Antioxidants are nutrients in food that protect human cells from damage from free radicals. Free radicals are unstable molecules that can damage human cells. Human body creates it when they digest food or breathe in pollution. Schiff base have potential to be one of the synthetic antioxidant agents. The objective of this research is to perform antioxidant activities on prepared Schiff base and Schiff base complexes. Antioxidant activity was carried out on previously synthesized Schiff base, Schiff base Tin and Schiff base Cobalt complexes. Briefly the DPPH scavenging activity was carried out by mixing solution of sample with DPPH and it kept in the dark place and have an optical density were measured at 517nm by using the Cecil-Elect Spectrophotometer. The antioxidant activity of Schiff base and Schiff base complexes was determined by DPPH free radical-scavenging assay. Highest antioxidant potential showed by Schiff base as compared to the Schiff base complexes from 1.95 μg/mI to 1000 μg/ml. One-way between subjects ANOVA was conducted to compare the antioxidant activity on different Schiff base and Schiff base complexes which showed significantly different free radical scavenging activity.